Handbook of swarm intelligence : concepts, principles and applications - Lim Meng-Hiot Lim; Panigrahi, Bijaya Kitan; Shi, Yuhui (Adaptation, learning, and optimization, 2011)
Recent work on the behavior of swarming creatures such as bees posits an innate collective intelligence that gives rise to myriad computational problem-solving techniques. This volume is both an introduction to the topic and a survey of leading-edge research